Case report: A novel intronic JMJD6 likely pathogenic variant (c.941+75G > T) associated with congenital eyelid coloboma in one of the identical twin sisters - Li, Xin; Zhang, Yuqi; Chai, Gang; Su, Weijie; Zhang, Yan (Frontiers in Genetics, 2025)
BackgroundCongenital eyelid coloboma (CEC) is a rare genetic disease, manifesting as a congenital partial or total defect of the eyelid. In this study, we report a pedigree with CEC caused by a novel pathogenic variant in JMJD6.Case reportThe proband was a 3-year-old girl who presented with a congenital coloboma of the left upper eyelid, accompanied by hypoplasia of the ipsilateral eyebrow. Karyotype analysis was normal. Whole-exome sequencing (WES) identified a novel pathogenic variant in JMJD6 (c.941+75G > T), which was classified as a likely pathogenic (LP) and de novo variant. To date, this variant has not been reported.ConclusionOur study found a novel pathogenic variant in JMJD6 (c.941+75G > T), which broadens the CEC phenotype spectrum and JMJD6 gene variant spectrum, providing a basis for clinical diagnosis, genetic counseling, and treatment.